Quality Evaluation of Plant-Derived Foods (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear Colleagues, It is well established that preference (but not exclusivity) for plant-derived foods can result in both health and environmental benefits. However, it must be acknowledged that not all plant-derived foods present the same quality to consumers. Hence, traditional and novel tools to assure high-quality standards have to be applied to these types of foods. At the same time, the definition of quality may be different from product to product and must be studied accordingly. Hence, the contents of bioactive compounds, amount of fat or fatty acid profiles, vitamins, carbohydrates, volatile compounds, and microbial safety or sensorial characteristics are some of the parameters that can provide an insight into plant-derived food quality. Of course, this type of food is usually subject to some kind of postharvest processing or storage, which can alter their properties. This has also led to the need to study how these procedures change the characteristics of the original food. This Special Issue on “Quality Evaluation of Plant-Derived Foods Ⅱ” focuses on the topic of the quality assessment of plant-derived foods. This includes novel approaches to this line of research, but also the use of the established methodologies for novel plant foods, understudied species, or new data on known plant foods.